Constitutive expression of spliced XBP1 causes perinatal lethality in mice. Issue 5 (23rd April 2021) - Xu, Qian; Zhang, Hua; Wang, Suzhen; Qin, Chunlin; Lu, Yongbo
Summary: Upon endoplasmic reticulum (ER) stress, inositol‐requiring enzyme 1 (IRE1) is activated and catalyzes nonconventional splicing of an unspliced X‐box binding protein 1 (XBP1U) mRNA to yield a spliced XBP1 (XBP1S) mRNA that encodes a potent XBP1S transcription factor. XBP1S is a key mediator of the IRE1 branch that is essential for alleviating ER stress. We generated a novel mouse strain (referred to as " Xbp1 CS/+ " mice) that constitutively expressed XBP1S after Cre recombinase‐mediated recombination. Further breeding of these mice with Twist2 Cre recombinase ( Twist2‐Cre ) knock‐in mice generated Twist2‐Cre ; Xbp1 CS/+ mice. Most Twist2‐Cre ; Xbp1 CS/+ mice died shortly after birth. Reverse‐transcription polymerase chain reaction (RT‐PCR) showed that constitutive expression of XBP1S occurred in various mouse tissues examined, but not in the brain. Immunohistochemistry confirmed that although the immunostaining signals for total XBP1 (XBP1U and XBP1S) were found in the calvarial bones in both Twist2‐Cre ; Xbp1 CS/+ and control mice, the signals for XBP1S were only detected in the Twist2‐Cre ; Xbp1 CS/+ mice, but not in the control mice. These results suggest that a precise control of XBP1S production is essential for normal mouse development.